Implementasi kebijakan persentase 60% pribumi dan 40% non-pribumi dalam penerimaan pekerja industri di kabupaten karawang - Fauzi, Indra Nirwan; Hakim, Lukmanul; Febriantin, Kariena (JURNAL MANAJEMEN, 2021)
In an effort to maximize its local manpower in the middle of industrial disruption, the Regency of Karawang uses 60:40 proportion (local and non-local respectively) scheme as written in Karawang Regency Local Regulation Number 1 of 2011 about Manpower Administration, and regulated further through Karawang Regent Regulation Number 8 of 2016 concerning Expansion of Employment Opportunities. These regulations was created in result of massive number of unemployment in midst of ever-growing industrial sector. The officials in Karawang Regency hoped that with these regulations, local citizens of Karawang could have a higher chance to be employed at a factory within Karawang administration. But in its implementation, several key problems are identified that can hinder the main goals of this regulation.Â  A number of problems, the background of this regulation, and several other factors are what interests meÂ  to analyze this regulation using qualitative research method.